ADAT PERKAWINAN MELAYU DESA IV KOTO SETINGKAI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Reki Rinaldo; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
It is very necessary to make efforts in the aspect of culture and local wisdom of the Malay community in IV Koto Setingkai Village, Kampar Kiri in forming the identity of the true Malay community. So that the current generation who tends to be ignorant, will be able to know, uphold, foster, preserve, and maintain the values contained in the Malay wedding customs of IV Koto Setingkai Village Kampar Kiri.The type of research is qualitative research with a field study approach (filed research). Data collection techniques through interviews, observations, and documentation studies. Informants were taken from traditional stakeholders, village officials, ulama, and the community. The results obtained that: First; The forms of the traditional Malay wedding procession of IV Koto Setingkai Village are: (a) Merisik, (b) Returning ba dunsanak, (c) Opening the sign, (d) Gathering Tunganai, (e) Delivery, (f) Bernai, (g) Marriage contract, and (h) Fresh flour. Second; The socio-cultural values of the community that become the essence of the traditional Malay marriage cultural procession of Desa IV Koto Setingkai are (a) Efforts to become a perfect human being,(b) Fostering relationships with God, fellow humans, and other creatures as well as nature,  (c) Maintaining kinship structure, (d) Becoming a person into Malay, (e) Giving birth to a quality generation, (f) Forming and maintaining Adat, and (g) Consistency in customary law. Based on the researcher's analysis that why the traditional marriage procession in IV Koto Setingkai Village is still sustainable, there are several strategies that are carried out, namely: (a) The activity of the customary government system, (b) Carrying out the customary marriage procession consistently by complying with customary law, and (c) Disseminate advice through oral poetry in an effort to inculcate values.Keywords: Culture, Marriage, Malay